New Principles of War : Enduring Truths with Timeless Examples - Pokrant, Marvin, 1943- (Book collections on Project MUSE., 2021)
"New Principles of War: Enduring Truths with Timeless Examples argues that the currently recognized principles of war are flawed, and proposes a new set of principles to guide military leaders"--